Samenhang in het interieur: de restauratie van de ontvangstkamer van de pastorie te Kockengen (Bulletin KNOB, 2000)
The Stichting Restauratie Atelier Limburg (SRAL) has taken care of the conservation of the reception room at Kockengen Roman Catholic vicarage. This front room is characterised by its painted wall-hangings. The wall-linings represent imaginative panoramic views of the typical Dutch polder landscape.Little is known about the history of the house and the successive inhabitants. Around 1800 a wealthy merchant, Martinus de Bruyn Jansz, owned the house. The front room was his formal drawing room. This merchant ordered the wall-linings from the Utrecht painter Henrick van Barneveld. The wall-linings are signed and dated 1802.SRAL undertook an architectural paint research in order to examine the paint layers on the panelling. Dark green vertical lines frame the wall-linings; therefore they were included in the architectural paint research. A small painted fragment was found on a wall post hidden behind the dado rail and was never repainted. It showed a fragment of the original decoration of the panelling: a greyish colour decorated with dark green vertical lines, and traces of yellow highlights. The dark green consisted of the same pigment compounds as the dark green lines on the wall-linings.After this thorough and structured survey SRAL handled the conservation of the wall-hangings. They were treated in situ because the examination pointed out they have never been removed. To remove them after two centuries only for this treatment was unnecessary, meaning that after treatment the wall hangings are still fixed with the early nineteenth century nails.SRAL also took care of the restoration of the chimneypiece, a neoclassical stucco relief representing merchant's attributes. The architectural paint research showed the chimneypiece had been decorated with a combination of two different layers of faux marble, hidden beneath a 20th century glossy white overpaint. This faux marble decoration was restored by removing the white overpaint.The project showed the advantages of a holistic approach. The wall linings were included by the architectural paint research and thus the decoration of the front room could be understood more completely, although it is not known how this decoration exactly looked like. The wall-linings are dominating the room and therefore it was accepted to reconstruct the grey colour on the panelling.Halfway the nineteenth century the house was turned into a Roman Catholic vicarage, which entailed inevitable alterations to the house and the front room. A new facade was erected and a third window was brought into the outer sidewall. These changes are to be respected. Looking at a room full of history with our 20th-century eyes, we will never be able to see the room in its 1802 appearance. Nevertheless, every action during the research and conservation was done with the unity the room once had in mind.